The Deadly Details: How Clear and Complete Are Publicly Available Sources of Human Rabies Information? - Natalie Patane; Owen Eades; Jennifer Morris; Olivia Mac; Kirsten McCaffery; Sarah L. McGuinness (Tropical Medicine and Infectious Disease)
Human rabies is preventable but almost always fatal once symptoms appear, causing 59,000 global deaths each year. Limited awareness and inconsistent access to post-exposure prophylaxis hinder prevention efforts. To identify gaps and opportunities for improvement in online rabies information, we assessed the readability, understandability, actionability, and completeness of online public rabies resources from government and health agencies in Australia and similar countries, with the aim of identifying gaps and opportunities for improvement. We identified materials via Google and public health agency websites, assessing readability using the Simple Measure of Gobbledygook (SMOG) index and understandability and actionability with the Patient Education Materials Tool for Print materials (PEMAT-P). Completeness was assessed using a framework focused on general and vaccine-specific rabies information. An analysis of 22 resources found a median readability of grade 13 (range: 10–15), with a mean understandability of 66% and mean actionability of 60%; both below recommended thresholds. Mean completeness was 79% for general rabies information and 36% for vaccine-specific information. Visual aids were under-utilised, and critical vaccine-specific information was often lacking. These findings highlight significant barriers in rabies information for the public, with most resources requiring a high literacy level and lacking adequate understandability and actionability. Improving readability, adding visual aids, and enhancing vaccine-related content could improve accessibility and support wider prevention efforts.